Genre analysis as a pre-instructional, instructional, and teacher development framework. Issue 19 (September 2015) - Cheng, An
Abstract: The framework of genre analysis described in Swales (1990) has become arguably the most influential one for analyzing EAP learners' target discourse and for developing learner-responsive EAP materials at the pre-instructional stage. What other roles can genre analysis play in EAP teaching and learning? In this paper, I present multiple excerpts from a student's genre analysis tasks and from my own analysis of the same journal article introduction that the student analyzed. I look closely at one 'incident' in which the student interpreted a statement in the genre exemplar as the authors' attempt to "create a gap of study." Elaborating on this 'incident, ' I argue that the genre analysis framework conceptualized by Swales (1990) can function simultaneously at three interacting levels: as a framework for analyzing learners' target discourse at the pre-instructional stage, as a framework for guiding learners to learn EAP writing during instruction, and as a framework for EAP teachers to continuously deepen their genre knowledge and their knowledge of students' target genres. I conclude by proposing two future research directions: focusing on studying learners who use genre analysis to learn EAP and focusing on learners' real needs in genre analysis research projects. Highlights: A student misinterpreted a statement in a journal article as the authors' attempt to "create a gap". Further analysis indicates the overemphasis of "creating a gap" in teaching and learning. The incident shows how genre analysis facilitates students' learning of genre-specific features. It also shows how genre analysis can help EAP teachers to deepen their genre knowledge.